Multivalent acetylated-sialic acid as recognition elements for the electrochemical sensing of viral antigens - Zhang, Zhen; Ji, Haijie; Zhuang, Xiwei; Xu, Yuning; Liu, Jianlei; Zeng, Chijia; Ding, Wen; Cui, Feiyun; Zhu, Sanyong (Biosensors & bioelectronics, 2025)
Electrochemical biosensors hold great promise for the rapid screening of viral infectious diseases. However, the recognition elements of these biosensors are typically limited to antibodies, aptamers, and molecularly imprinted polymers. In this study, acetylated sialic acids were explored as recognition elements because they serve as natural viral receptors expressed on host cells. Specifically, 4-O-acetylated-SA (4-O-Ac-SA) and 9-O-Ac-SA, were synthesized selectively, and their binding affinity with the SARS-CoV-2 S antigen was examined. The S antigen tended to bind to 9-O-Ac-SA. Additionally, the biocompatibility and neutralizing effects of 4/9-O-Ac-SA on the S antigen were validated. The validation demonstrated that 9-O-Ac-SA could efficiently inhibit S antigen binding to host cells. The cluster glycoside effect of the recognition between the S antigen and 9-O-Ac-SA was validated. Subsequently, an electrochemical biosensor for the rapid screening of viral antigens was developed using 9-O-Ac-SA as the recognition element. The application of electrochemical impedance spectroscopy as a readout method allowed for the identification of the S antigen at concentrations of 10 ng/mL with acceptable stability and repeatability. The biosensor demonstrated a strong linear response over the range of 10∼1 × 104 ng/mL. In summary, the study presented a promising recognition element for the development of electrochemical biosensors for rapid viral infection screening. The utilization of glycans for viral antigen detection could pave the way for innovative advances in electrochemical biosensor technology.